2011
DOI: 10.2139/ssrn.1755748
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Social Media: Persistence and Decay

Abstract: Social media generates a prodigious wealth of real-time content at an incessant rate. From all the content that people create and share, only a few topics manage to attract enough attention to rise to the top and become temporal trends which are displayed to users.The question of what factors cause the formation and persistence of trends is an important one that has not been answered yet. In this paper, we conduct an intensive study of trending topics on Twitter and provide a theoretical basis for the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
198
1
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 13 publications
9
198
1
12
Order By: Relevance
“…However, in order to restore the original topic sequence, it is important to know the exact shape of srf (t). To model the shape of srf (t), we propose to employ a family of normalized decaying functions (Asur et al 2011) demonstrated in the following equations:…”
Section: Modelling Impacting Topicsmentioning
confidence: 99%
“…However, in order to restore the original topic sequence, it is important to know the exact shape of srf (t). To model the shape of srf (t), we propose to employ a family of normalized decaying functions (Asur et al 2011) demonstrated in the following equations:…”
Section: Modelling Impacting Topicsmentioning
confidence: 99%
“…For that reason, a ghost followers industry exists for the sole purpose of increasing social proof on social media [27]. However, Sitaram Asur et al [28] empirically discovered that number of followers do not contribute to trend creation. Similarly, Thackeray et al [29] found that 'liking' the page does not result in purchasing the product.…”
Section: Social Proofmentioning
confidence: 99%
“…El comportamiento de los usuarios que hace de un tuit o un tema se convierta en trending topic se basa más en el contenido que no en los atributos del usuario (Asur, Szabo, Huberman & Wang, 2011).…”
Section: Patrones De éXito En Redes Socialesunclassified